Experimental study on demountable shear connectors in composite slabs with profiled decking. (July 2016) - Rehman, N.; Lam, D.; Dai, X.; Ashour, A.F.
Abstract: This paper presents an experimental study on shear strength, stiffness and ductility of demountable shear connectors in metal decking composite slabs through push-off tests. Twelve full-scale push-off tests were carried out using different concrete strength, number of connectors and different connector diameter. The experimental results showed that the demountable shear connectors in metal decking composite slabs have similar shear capacity and behaviour as welded shear studs and fulfilled the minimum ductility requirement of 6 mm required by Eurocode 4. The shear capacity was compared against the prediction methods used for the welded shear connections given in Eurocode 4, AISC 360-10, ACI 318-08 and method used for bolted connection in Eurocode 3. It was found that the AISC 360-10 method overestimated the shear capacity while the ACI 318-08 method underestimated the shear capacity of specimens with single shear connector per trough. The Eurocodes method was found to provide a safe prediction for specimens with single and pair demountable connectors per trough. In addition, prediction methods given in both AISC 360-10 and ACI 318-08 for welded shear studs overestimated the shear capacity of specimens with 22 mm diameter demountable connectors that failed in concrete crushing. Highlights: Behaviour of demountable shear connectors in profiled metal deck composite flooring Experimental studies on demountable shear connectors Parameters affect the behaviour of demountable shear connectors. Proposed equations to evaluate the shear capacity of demountable shear connectors